Money vs. time: Family income, maternal labor supply, and child development - Francesco Agostinelli; Giuseppe Sorrenti (University of Zurich, Department of Economics, 2021)
This paper analyzes the relationship between work-promoting policies and child development. First, we provide new comprehensive evidence of the unintended consequences for child development of the Earned Income Tax Credit expansions during the 1990s in the United States. Second, our theory-driven empirical model reconciles this result by shedding light on the trade-off between the income effect (economic resources) and the substitution effect (time and quality of the parent-child interactions) on a child's cognitive and behavioral development. This money versus time trade-off is most pronounced for disadvantaged mothers. Overall, our results call for a policy debate on how to design targeted supplements for disadvantaged families to support working mothers and their children.
Keywords: H24; H31; I21; I38; J13; J22; 330; Child development; family income; maternal labor supply; Kognitive Entwicklung; Verhaltensentwicklung; Arbeitsangebot; Mutter; Einkommen; Kinderbetreuung; Mindestlohn